Complex Hemograms of Isolator Raised Specific Pathogen Free (SPF) Chicks - Cotter , Paul F.; Heller, E.D. (International Journal of Poultry Science, 2016)
Heterophil/lymphocyte (H/L ratio) statistics and total white blood cell counts (TWBC) determined by light microscopic examination of blood from isolator raised specific pathogen free (SPF) chicks indicated complex hemograms. Brachial vein blood (N =12) obtained at 6 wk was spread into films, air dried, post-fixed in MeOH and Wright’s stained. H/L 1 ratios were calculated by dividing all heterophil types, typical (HT) variant (HV) and classic (HC) by the number of small (resting) lymphocytes (Ls) H/L 1 = (HT + HV + HC)/(Ls). A second ratio (H/L 2) obtained by dividing heterophils by all lymphocytes (resting, reactive and atypical, (HT + HV + HC)/ (Ls + Lm) was calculated; as was the H/L 1-H/L 2 difference (ΔH/L). TWBC’s were determined from the same films. Sorting, non-random distribution of cells and atypia affected all H/L statistics. The mean H/L 1 ratio from standard differential counts (SDC) = 0.17 and H/L 2 = 0.16. Edge based ratios (EB) were ~8 times the SDC values. Atypical cells were in all samples and more common in EB counts. The H/L ratios and ΔH/L calculated from SDC and EB values were significantly different (p